Functional traits determine plant co-occurrence more than environment or evolutionary relatedness in global drylands - Soliveres, Santiago (2014)
Plant–plant interactions are driven by environmental conditions, evolutionary relationships (ER) and the functional traits of the plants involved. However, studies addressing the relative importance of these drivers are rare, but crucial to improve our predictions of the effects of plant–plant interactions on plant communities and of how they respond to differing environmental conditions. To analyze the relative importance of – and interrelationships among – these factors as drivers of plant–plant interactions, we analyzed perennial plant co-occurrence at 106 dryland plant communities established across rainfall gradients in nine countries. We used structural equation modelling to disentangle the relationships between environmental conditions (aridity and soil fertility), functional traits extracted from the literature, and ER, and to assess their relative importance as drivers of the 929 pairwise plant–plant co-occurrence levels measured. Functional traits, specifically facilitated plants’ height and nurse growth form, were of primary importance, and modulated the effect of the environment and ER on plant–plant interactions. Environmental conditions and ER were important mainly for those interactions involving woody and graminoid nurses, respectively. The relative importance of different plant–plant interaction drivers (ER, functional traits, and the environment) varied depending on the region considered, illustrating the difficulty of predicting the outcome of plant–plant interactions at broader spatial scales. In our global-scale study on drylands, plant–plant interactions were more strongly related to functional traits of the species involved than to the environmental variables considered. Thus, moving to a trait-based facilitation/competition approach help to predict that: (1) positive plant–plant interactions are more likely to occur for taller facilitated species in drylands, and (2) plant–plant interactions within woody-dominated ecosystems might be more sensitive to changing environmental conditions than those within grasslands. By providing insights on which species are likely to better perform beneath a given neighbour, our results will also help to succeed in restoration practices involving the use of nurse plants.